2010
DOI: 10.1103/physrevlett.104.156402
|View full text |Cite
|
Sign up to set email alerts
|

Forcing Ferromagnetic Coupling Between Rare-Earth-Metal and3dFerromagnetic Films

Abstract: Using density functional calculations, we have studied the magnetic properties of nanocomposites composed of rare-earth-metal elements in contact with 3d transition metals (Fe and Cr). We demonstrate the possibility to obtain huge magnetic moments in such nanocomposites, of order 10mu(B)/rare-earth-metal atom, with a potential to reach the maximum magnetic moment of Fe-Co alloys at the top of the so-called Slater-Pauling curve. A first experimental proof of concept is given by thin-film synthesis of Fe/Gd and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…This then raised the possibility of an overall ferromagnetic (FM) coupling between the 3d transition magnetic metal such as Fe and the RE. This was supported by density functional theory calculations that informed the synthesis of a series of Gd/Cr/Fe multilayer systems 11 . Examination of the multilayers with X-ray magnetic circular dichroism (XMCD) measurements identified coupling as evidenced by changes in the T c of the multilayer system.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…This then raised the possibility of an overall ferromagnetic (FM) coupling between the 3d transition magnetic metal such as Fe and the RE. This was supported by density functional theory calculations that informed the synthesis of a series of Gd/Cr/Fe multilayer systems 11 . Examination of the multilayers with X-ray magnetic circular dichroism (XMCD) measurements identified coupling as evidenced by changes in the T c of the multilayer system.…”
mentioning
confidence: 87%
“…External corroboration of the observation that a parasitic fcc phase is present and so degrades functional magnetic response occurs if we revisit the microstructure of the originally proposed Gd/Cr/Fe where a more recent report clearly indicated that at the thickness (4.34nm) of Gd employed there is a similarly large fraction of the Gd fcc phase present 24 , though it is not indexed. Consequently, taking our data here along with the absence of functional data in other work 11,24 we believe that "huge magnetization" of such RE/M/FM multilayers cannot be practically realized until this paramagnetic portion can be removed from the Gd or other RE film in such multilayers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrathin RE magnetic films and multilayers have also attracted attention due to their ability to induce perpendicular magnetic anisotropy in adjacent transition-metal layers [11], control magnetic damping in spin valve devices [12,13], as well as fabricate materials with higher magnetization compared to transition-metal alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%